Latitudinal patterns in the diversity of two subgenera of the genus Daphnia O.F. Müller (Crustacea: Cladocera: Daphniidae) - Popova, Ekaterina Y.; Kotov, Alexey A. (Zootaxa, 2013)
Daphnia O.F. Müller (Crustacea: Cladocera: Daphniidae) is an important model in biology. It was concluded earlier that subgenus Daphnia s.str. occurs mainly in the northern hemisphere, subgenus Daphnia (Ctenodaphnia) in the southern hemisphere, which could suggest that: (1) the subgeneric differentiation is correlated with the Laurasia-Gondwanaland subdivision and (2) D. (Ctenodaphnia) is a taxon of Gondwanian origin. Some authors even discussed mechanisms of maintaince of the “ancient subgeneric north-south split”, regarding such a pattern as paradoxical. But both molecular clock calculations and fossils of both subgenera from the Jurassic/Cretaceous boundary of Mongolia compromise such ideas and suggest an earlier, Pangaean, differentiation of the subgenera. We discuss the distribution of Daphnia worldwide based on recent literature. Our analysis covers literature data on all described and on undescribed taxa revealed by genetical methods. Distributional data were associated with five main zones: southern cold (I), southern temperate (II), tropical (III), northern temperate (IV), and northern cold (V) zone. We found no “subgeneric north-south split”: the distribution of Daphnia s.str. is dissymmetric between the hemispheres (antipolar), while that of Ctenodaphnia is sub-symmetric (bipolar). We suggest that both patterns are not of Mesozoic, but of Cenozoic origin. Mesozoic differentiation of the subgenera does not contradict a recent origin of the extant species, as found in e.g. Notostraca. A superficially attractive hypothesis about a Gondwanian origin of a taxon (Daphnia (Ctenodaphnia)) therefore did not pass the test of the fossil records. In addition, we agree with the opinion that an antipolar is only a variant of a bipolar pattern, as a result of an extinction in the southern hemisphere, and that these patterns are mid-late Cenozoic instead of Mesozoic.